"Addressing the wear problem in the Cologne Grape Distillation Heat exchanger" (Damascus University Journal for engineering sciences, 2025)
The copper tubes in the heat exchanger suffer from the problem of corrosion in the colon device for distilling grapes، which causesobstacles in the production process and high maintenance costs.Therefore، this research was studied to determine the causes of corrosion and ways to prevent them. The corrosion rate was calculated by the weight loss method by the age method in the corrosion media taken from the alcoholic beverages factory (Al- Rayyan Factory). Stainless steel also tested in the same media and the same time period. It was observed that the corrosion value of the copper sample immersed in water was higher compared to the two samples immersed in ferment and distilled grape juice. The corrosion rate was calculated for the copper sample immersed in water، its value was 0.039 mm/y، the corrosion rate for the copper sample immersed in distilled grape juice was 0.0126 mm/y. and the corrosion rate for the copper sample immersed in fermented grape juice was mm/y. The acidity of the water was tested during multiple periods and determined its value is    ph =5. The chemical composition of a sample taken from the copper tube used in the heat exchanger was analyzed. 0.0024 mm/y the cause of corrosion was found to be due to the low hardness of the water، and the temperature difference between water and alcohol، the acidity of the grape juice. It was also found during the test period that the stainless steel samples did not corrode، while the copper sample do it.
Keywords: copper; carbon steel; heat exchanger; corrosion phenomenon